Stylistic Study of The One-Wing Eagle Anthology by Ulfatin C.H with A Semiotic Approach - Sigit Andi Prasetya Dinata; Dwi Setiyawan; Dini Nurhayati (International Journal of Science and Applied Science: Conference Series, 2021)
The poetry anthology ‘Rajawali Satu Sayap’ by Ulfatin C.H in this research is studied from the stylistic aspect using semiotic approach. This research aims to find and analyse stylistic elements such as diction, imagery, figurative language, and meaning found in the poetry anthology ‘Rajawali Satu Sayap’ by Ulfatin C.H. Descriptive qualitative method with content analysis technique is the method used in this research. The meaning of the signalling system and language signs in the poems is revealed through a semiotic approach. The results show some stylistic peculiarities in the anthology ‘Rajawali Satu Sayap’, including (1) the use of diction dominated by connotative and philosophical words, (2) the use of strong images, especially visual and kinesthetic images, (3) the use of figurative language dominated by metaphor and personification, and (4) meanings that describe life struggles, spirituality, and social criticism. This study contributes to the development of stylistic studies of modern Indonesian poetry using a semiotic approach.